Frontal Sinusitis with Mixed Bacterial Colonies Treated with the Combination of Endoscopic Modified Lothrop Procedure and External Approach. (9th December 2013) - Nomura, Kazuhiro; Honkura, Yohei; Okumura, Yuri; Kasajima, Atsuko; Suzuki, Takahiro; Kikuchi, Toshiaki; Hidaka, Hiroshi; Oshima, Takeshi; Katori, Yukio
Abstract : Isolated frontal sinusitis with mixed bacterial colonies is extremely rare and has not been described. We report a case of isolated frontal sinus forming mixed bacterial colonies that occurred in the previously exposed frontal sinus. The material in the frontal sinus was macroscopically similar to sinus fungus ball. Surgical strategy followed that for sinus fungus ball. The material could not be completely removed even with an endoscopic modified Lothrop procedure (Draf type III procedure). Additional external incision enabled complete removal of the remnant infectious substance. Histological examination detected two different types of organisms as intermingled bacterial colonies. External approaches to the frontal fungus ball have recently been replaced by the endonasal approach. Our case suggests that material trapped in a pit or small crevice in a frontal sinus may not be removed intranasally.